Modelling Foundations and Applications 9th European Conference, ECMFA 2013, Montpellier, France, July 1-5, 2013. Proceedings - Gorp, Pieter; Ritter, Tom.; Rose, Louis M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 9th European Conference on Modelling Foundations and applications, ECMFA 2013, held in Montpellier, France, in July 2013. The 15 papers presented in this volume were carefully reviewed and selected from 51 submissions. They are on all aspects of MDE, including topics such as model querying, consistency checking, model transformation; and model-based systems engineering and domain-specific modeling.
Employing the Object Constraint Language in Model-Based Engineering -- MOCQL: A Declarative Language for Ad-Hoc Model Querying -- Supporting Different Process Views through a Shared Process Model -- Characterization of Adaptable Interpreted-DSML -- Transformation as Search -- Model-Based Generation of Run-Time Monitors for AUTOSAR -- End-User Support for Debugging Demonstration-Based Model Transformation Execution -- DPMP: A Software Pattern for Real-Time Tasks Merge -- Using Model Types to Support Contract-Aware Model Substitutability -- Applying a Def-Use Approach on Signal Exchange to Implement SysML Model-Based Testing -- A Network-Centric BPMN Model for Business Network Management -- Design Management: A Collaborative Design Solution -- Umbra Designer: Graphical Modelling for Telephony Services -- Experience with Industrial Adoption of Business Process Models for User Acceptance Testing -- A Case Study in Evidence-Based DSL Evolution -- Model Driven Software Development: A Practitioner Takes Stock and Looks into Future.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Management of Computing and Information Systems; Programming Techniques